Analysis of The Effectiveness of Internal Auditors in Overcoming Fraud in PT Midi Utama Indonesia - Hernawaty; Suwarno; Elmo Novera (Yayasan Multidimensi Kreatif, 2024)
This study aims to analyze the effectiveness of the role of internal auditors in overcoming fraud at PT Midi Utama Indonesia Medan branch. Fraud is a problem that negatively impacts the company's performance and sustainability. Fraud is an action that directly or indirectly causes a company's losses in financial and non-financial forms. The role of internal auditors is important in identifying and controlling fraud risks as one of the preventive fraud prevention. This study uses a case study method with a qualitative approach. The data collection process was through intense interviews with internal auditors, managers, and company employees. Then an analysis of documents related to internal control procedures and audit reports was carried out. The results of the study show that PT Midi Utama Indonesia's internal auditors have played an effective role in overcoming fraud. Internal auditors conduct regular audits, provide recommendations for improvement, and monitor follow-up on audit findings. In addition, internal auditors also play a role in increasing employee awareness of the importance of integrity and work ethics. This study resulted in the conclusion that the role of internal auditors has been effective, where during a period of 3 years (2016-2018) fraud acts that occurred decreased by 25% in 2017, and decreased by 19% in 2018. However, there are still some obstacles faced by internal auditors, such as limited resources and lack of top management support. Therefore, a strong commitment from all levels of management is needed to support the role of internal auditors in preventing and detecting fraud more effectively.